Growth of National Parks Information Knowledge for Improving Biodiversity Conservation in Bangladesh: An Outlook on Policy Perspectives - Md. Rahimullah, Miah; Alexander Kiew, Sayok; Ahi, Sarok; Mohammad Belal, Uddin (Hindawi Publishing Corporation, 2017)
In Bangladesh, biodiversity loss is a national issue, which connects with the high biological productivity of parks, wildlife sanctuaries, wetlands, homestead forests and marine biota. National Parks Information (NPI) are the state hubs of biodiversity conservation systems. Everyone exploits this biodiversity but none can effectively conserve due to lack of methodically policies and tools. This study attempts to augment knowledgeable factors of the policies towards growth of national parks for conserving biodiversity in Bangladesh. It also represents on the analysis and review of the current distribution of national parks, policy tools and legal aspect to enhance conservation activities within and around the areas. The research data collected through literature reviews, observations, interviews, and stakeholder’s participation. The study illustrated that existing NPs are disseminated among 27.13% of administrative district areas, but no NPs in 72.87% districts in Bangladesh which will have adverse effect on future biodiversity conservations. The study focused that the growth of NPI which highlighted within the period of 2010 to 2014. The research also found that Lawachara National Park is in good conditions compared to other NPs in Sylhet division. Moreover, the study recommends that the policy-making decisions on sustainable biodiversity protection at NPs in Bangladesh should integrate the national growth with economic, social, 4 institutional, environmental and legislative domains. It concludes by highlighting conceptual changes for integrative biodiversity research at national parks.